2022
DOI: 10.1140/epjs/s11734-022-00540-7
|View full text |Cite
|
Sign up to set email alerts
|

Complex bio rhythms

Abstract: Complex biorhythms are characteristic of ubiquitous phenomena appearing in many disciplines of human knowledge. This Special Issue collects articles devoted to different complex biorhythms phenomena such as cardiac dynamics, Covid-19 dynamics, dynamics of neural networks, cell dynamics, and a few articles devoted to general methods. It furnishes a rich overview of the field and can stimulate and inspire further researches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Physiologically, normal compliance of the heart depends on the regularity of the system. References [9][10][11][12][13] have shown that the construction of synthetic ECGs can reveal a variety of responses, including normal and pathological rhythms. In a similar vein, Norbert Wiener and Arturo Rosenblueth, in their work on the mathematical formulation of the problem of impulse conduction in a network of connected excitable elements, notably in cardiac muscle, demonstrated the importance of the spatial role of depolarization waves on cardiac tissue, beyond just the SA and AV nodes, and the His bundles and Purkinje fibers [14].…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, normal compliance of the heart depends on the regularity of the system. References [9][10][11][12][13] have shown that the construction of synthetic ECGs can reveal a variety of responses, including normal and pathological rhythms. In a similar vein, Norbert Wiener and Arturo Rosenblueth, in their work on the mathematical formulation of the problem of impulse conduction in a network of connected excitable elements, notably in cardiac muscle, demonstrated the importance of the spatial role of depolarization waves on cardiac tissue, beyond just the SA and AV nodes, and the His bundles and Purkinje fibers [14].…”
Section: Introductionmentioning
confidence: 99%
“…The heart rhythm is governed by the flow of this impulse as it passes through the heart and allows all the structures of the heart to contract synchronously. This is the regulatory core of the heart rhythm [ 15 , 16 ]. In the cardiac system, the node of origin of the electrical impulse is the sinus node, also known as the natural pacemaker.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the inner electromagnetic field energy is changed by external physical stimuli. From dynamical viewpoint, external stimuli and even noisy disturbance can induce distinct mode transition in the oscillatory state [28]. The cell membrane shows some properties of capacitor with controllable capacitance because of its flexibility, the ion channels embedded into the cell membrane show some properties of inductors with adjustable inductance because its activation is controllable (active or blocking).…”
Section: Introductionmentioning
confidence: 99%